An agent-oriented information processing architecture for sensor network applications. (25th May 2006) - Biswas, Pratik K.; Schmiedekamp, Mendel; Phoha, Shashi
In this paper, we present a hybrid, multi-layered, agent-based architecture for distributed sensor networks. We propose a middleware that integrates the programmable application layer consisting of software agents with the physical layer consisting of extremely small, low-powered sensor nodes. We discuss two major middleware components, namely, C3L: a distributed command and control language with its interpreter and STACS: a programmable controller synthesiser. We explain how C3L can be used to command and control sensor network operations and STACS to configure the behaviour of a node. We provide frameworks for communication, mobility and data management, as primary means for information dissemination and fusion. We suggest an agent model that integrates the software agents of the application with the hardware agents of the physical environment. We describe a simplified, integrated surveillance experiment to illustrate an implementation of this information processing architecture. Finally, we conclude with an insight to future challenges.